Influence of Zirconia Interfacial Coating on Alumina Fiber‐reinforced Alumina Matrix Composites. Issue 2 (25th October 2012) - Licciulli, Antonio; Chiechi, Antonio; Fersini, Maurizio; Sanosh, Kunjalukkal P.; Balakrishnan, Avinash
<x xml:space="preserve">Abstract</x> The present study demonstrates an approach for fabricating fiber‐reinforced ceramic matrix composites (CMCs) involving the coating of 2‐dimensional woven alumina fibers with zirconia layer by sol gel, followed by impregnation of these coated fibers with alumina matrix and pressureless sintering. To emphasize the benefits of the zirconia coating on these CMCs, a reference sample without interfacial coating layer was prepared. The zirconia‐coated CMCs showed superior flexural strength and thermal shock resistance compared with their uncoated counterparts. Foreign object damage tests carried out on the ZrO2 coated CMCs at high impact speed showed localized damage without any shattering.